The Effect of Hedonic Shopping Value, Lifestyle, and Fear of Missing Out (FOMO) on Consumer Behavior of Fashion Products on Shopee - Vera Rahmawati; Jaya Ramadaey Bangsa (Golden Ratio of Data in Summary, 2026)
The development of e-commerce drives changes in consumer behavior, especially increased consumption when purchasing fashion products online. This study aims to analyze the influence of Hedonic Shopping Value, Lifestyle, and Fear of Missing Out (FoMo) on Consumptive Behavior on Fashion Products on the Shopee E-commerce Platform. This study uses a quantitative, correlational method. Data were collected through questionnaires distributed to Shopee users who had purchased fashion products. The sampling technique used was purposive sampling, with a total of 140 respondents from Bojonegoro Regency selected to meet the research criteria. The data were analyzed using correlation analysis to test the influence of each independent variable on Consumptive Behavior. The test results indicate that the Hedonic Shopping Value variable has a positive and significant effect on Consumptive Behavior (p-value = 0.000), supporting the hypothesis. The Lifestyle variable also has a positive and significant effect on Consumptive Behavior (p-value = 0.024), supporting the second hypothesis. Furthermore, Fear of Missing Out (FoMO) was found to have a positive and significant influence on Consumer Behavior (p = 0.000), thereby accepting the third hypothesis. Based on these research results, it can be concluded that psychological and lifestyle factors play a significant role in driving Consumer Behavior on e-commerce platforms. These findings are expected to serve as a reference for business actors in designing more effective marketing strategies and for future researchers in developing studies related to Consumer Behavior.